High resolution measurements reveal abiotic and biotic mechanisms of elevated nitric oxide emission after wetting dry soil. (September 2021) - Slessarev, Eric W.; Greene, Aral C.; Homyak, Peter M.; Ying, Samantha C.; Schimel, Joshua P.
Abstract: Wetting dry soil triggers emission of nitric oxide (NO), which can harm air quality and influence ecosystem N balance. NO released after wetting may be derived from two primary mechanisms: (1) abiotic decomposition of nitrite (NO2 − ) present in the dry soil and (2) biologically-mediated production of NO. The relative contributions of these mechanisms to NO emission are challenging to partition. To differentiate the two mechanisms, we made continuous observations of NO emission from a range of soils that varied in texture, pH, and exchangeable cations. We coupled NO gas exchange measurements with automated, non-destructive high-resolution sampling of inorganic N species via microdialysis. We identified two distinct phases of NO production (1) an initial phase that reached its maximum less than 30 min after rewetting; and (2) a second phase lasting up to 36 h. The magnitude of the initial phase of NO production was correlated with the initial nitrous acid concentration (calculated from NO2 − concentrations and soil pH) and soil exchangeable calcium. The second phase of NO emission coincided with a peak in NO2 − that preceded NO3 − accumulation. Together, these results suggest that NO emissions following wetting are defined by an initial pulse of abiotic NO formation mediated by soil acidity at mineral surfaces, followed by a prolonged pulse of NO emission driven by a lag between the biological processes of ammonia oxidation and nitrite oxidation. These results can inform mechanistic models of NO emissions from soils to improve predictions of the terrestrial N cycle and atmospheric chemistry. Highlights: After wetting dry soil, nitric oxide (NO) is emitted in two distinct phases. Chemodenitrification of NO2 − drives NO emission immediately after wetting. NO2 − build up contributes to NO emission later after wetting.